Accuracy of the ETDQ-7 Questionnaire for Identifying Persons with Eustachian Tube Dysfunction - Teixeira, Miriam S (Otolaryngol Head Neck Surg, 2017)
OBJECTIVE: Compare the accuracy of the Eustachian Tube Dysfunction Questionnaire-7 (ETDQ-7) in identifying people with Eustachian tube (ET) dysfunction based on symptoms and based on an objective ET function test. STUDY DESIGN: Cross-sectional study. SETTING: Tertiary referral center. SUBJECTS AND METHODS: 55 subjects with and without symptoms suggestive of ET dysfunction completed the ETDQ-7 questionnaire and had their ET function evaluated by the percentage of middle ear pressure equilibrated after 5 swallows (PEq(5)) either during a Pressure Chamber test (intact tympanic membranes) or by the Inflation-Deflation test (non-intact tympanic membranes). The ETDQ-7 score ≥ 14.5 and PEq(5)<60% were used to define ET dysfunction and sensitivity, specificity and Receiver Operating Characteristic curves were used to assess the level of association between ETDQ-7 scores and PEq(5). RESULTS: 25 asymptomatic (Group 1= 15 females, 15 whites, mean age 32±12.8 years) and 30 subjects with ET dysfunction symptoms (Group 2= 17 females, 25 whites, mean age 27±16.3 years) were included in the analysis. ETDQ-7 sensitivity and specificity regarding correct group assignment were 70% and 100% and with respect to predicting PEq(5)<60%, 54% and 78% respectively. An area under the curve (AUC) of 0.68 (95% CI 0.53–0.83) at the participant level and of 0.64 (95% CI 0.50–0.77) at ear level indicated a moderate level of association which was lower, although not statistically significant, for non-intact tympanic membranes (AUC=0.63 at participant and AUC=0.49 at ear level). CONCLUSION: The ETDQ-7 score had higher correlation with ET dysfunction symptoms than with an objective measure of ET function.